1835 Mo. Rev. Stat. 312, An Act to Restrain Intercourse with Indians, § 2. - (:unkn) unknown (General Publisher, 1835)
IF any person shall induce any Indian to come within this state fro the purpose of trade, or otherwise than is hereinafter permitted, or shall purchase or receive of any Indian the way of trade or otherwise, a horse or gun, he shall be fined in a sum not exceeding fifty dollars.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES